Is coracohumeral distance associated with pain-function, and shoulder range of movement, in chronic anterior shoulder pain? - S. Navarro-Ledesma; F. Struyf; M. T. Labajos-Manzanares; M. Fernandez-Sanchez; A. Luque-Suarez (BMC Musculoskeletal Disorders, 2017)
Abstract Background The aim of this study was twofold: (i) to assess the intrarater reliability of coracohumeral distance; (ii) to investigate the level of association between coracohumeral distance measured by ultrasonography, and pain-disability and shoulder range of movement, in patients suffering from chronic anterior shoulder pain. Methods An observational, cross sectional study was carried out. A convenience sample comprised of 87 patients with chronic anterior shoulder pain was assessed from 3 primary care centres. Main outcomes as pain and function were measured through the shoulder pain and disability index. Furthermore, shoulder range of movement-free of pain in shoulder elevation, as well as coracohumeral distance at both 0 and 60 degrees, were collected. Results Absence of any correlation was found between coracohumeral distance and shoulder pain and disability index at both 0 and 60 degrees of shoulder elevation. Furthermore, absence of any correlation was found between coracohumeral distance measurements and active shoulder range of movement -free of pain. Conclusions There was poor association between coracohumeral distance and shoulder pain and function, as well as with shoulder range of movement, in patients with chronic anterior shoulder pain. Hence, clinicians should consider, not only increasing this space, but also other possibilities in their therapies, when patients with anterior shoulder pain are treated. Trial registration ACTRN12614000144617 . Registered: 1st March 2014.